Association between pre-operative high sensitive C-reactive protein and immediate post-operative radicular pain following prolapsed lumbar intervertebral disc surgery - Razib, K. Olinur; Rahman, Asifur; Farid Raihan, Mohammad; Shahnawaz Bari, Mohammad; Rahman, M. Ataur; Ahmmed, Tayeb; Saiful Islam, Kazi; Saiful Islam, Muhammad; Rahim, M. Abdur; Fatima, Kanij; Deb Nath, Haradhan (International Journal of Research in Medical Sciences, 2024)
Background: Nerve root compression is often inadequately understanding radicular pain due to prolapsed lumbar intervertebral disc, a common neurosurgical presentation. Inflammation is proved as an important etio-pathological component of radiculopathy, even after surgery. Methods: This cross-sectional intervention study conducted from March 2022 to September 2023. Data collected from 45 patients with prolapsed lumber intervertebral Disc, who underwent surgical intervention in Department of Neurosurgery, BSMMU. Results: The mean±SD age of the patients was 38.4±11.6 years, most of them 37 (82.2%) aged within 29 to 60 years. Majority 30 (66.7%) of them were male. Patients presented with pain, numbness and weakness was 45 (100%), 33 (73.3%) and 8 (17.8%) respectively. Among the participants most 36 (80%) had right sided and 9 (20%) had left sided radiation. The mean±SD level of pre-operative high sensitive C-reactive protein was 2.1±1.7. Pre-operative high sensitive C-reactive protein was significantly associated pre-operative, post-operative and mean change in visual analogue score (p<0.001, p<0.001, p= 0.006 respectively). Correlation of high sensitive C-reactive protein and VAS score (both pre and post-operative) were also statistically significant with p =0.017 and p <0.001 respectively. Conclusions: In our study, there is an association between pre-operative serum high sensitive C- reactive protein and post-operative radicular pain following surgical intervention in patients with prolapsed lumbar intervertebral disc.